A Design project on the manufacture of bond paper from bamboo - Abueg, Lino G.; Dungca, Danilo G.; Ramos, Zenaida R. (Quezon City College of Engineering, 1975)
Capacity: 40,800 MT/year -- Plant area: 500- x 400- feet -- Total fixed capital investment: P 171,133,250 -- Total capital investment: P 190,148,064 -- Total manufacturing cost: P 117,096,401 -- Annual sales at maximum production: P 149,328,000 -- Annual profit: P 32,231,599 -- Return on investment: 16.95% -- Pay-out time: 5.2 years -- Break even point: 13%
Typescript.
Submitted in partial fulfillment of the requirements for the degree of Chemical Engineering.
Keywords: Factories -- Design and construction; Paper products